Enhancing Prospective Teachers' Skills in Designing Physics Learning: Developing Electronic Learning Materials with Interactive Reading, Scaffolding and Modeling (IRTaMS) Strategies - Nurhayati, Nurhayati; Wahyudi, Wahyudi; Suhandi, Andi; Muslim, Muslim; Kaniawati, Ida; Saputri, Dwi Fajar (UIN Fatmawati Sukarno Bengkulu, 2026)
This study explores the development and implementation of electronic learning materials with interactive reading, scaffolding, and modelling (IRTaMS) strategies to improve the knowledge and skills of prospective physics teachers in designing learning that refers to the 4C skills-oriented Problem-Based Learning (PBL) model. This study uses the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects involved 24 prospective teachers of the Physics Education Program at a university in West Kalimantan with a pre-experimental one-group pre-test–posttest design. The research instruments included expert validation sheets, attitude scales, knowledge tests, and skill assessment rubrics. Data analysis includes; analysis of the validity of learning products using Aiken's V coefficient from expert judges' scores, percentage analysis to determine the level of readability, Wilcoxon Test to measure the significance of the difference between pre-test and post-test (including pre-task and post-task), and analysis of the average N-Gain (<g>) to determine the extent of the increase in knowledge and skills of prospective teachers. The results of expert validation and user responses indicate that electronic learning materials with IRTaMS strategies have a high level of validity and readability. The results of the study also showed a significant increase in the knowledge and skills of prospective teachers in designing PBL-based physics learning oriented to 4C skills, as reflected in the N-Gain value in the medium to high category. Skills improvement includes the formulation of learning objectives, criteria for achieving learning objectives, teaching materials, assessment planning, media use, and learning stages. The research findings indicate that the integration of IRTaMS strategies in digital technology-based electronic learning materials has strong potential in strengthening the pedagogical competence of prospective physics teachers, although comparative exploration with a control group is still needed in further research. This study contributes to the development of digital learning innovations through practical and contextual approaches to support 21st-century physics learning.